Cultivating an Entrepreneurial Spirit: Evaluation of Project-Based Learning in Increasing Students' Entrepreneurial Spirit - Ela Rizka Yulandari; Tran Huy Duc; Suwakhon Somphaiphithak (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The aim of this research is to evaluate the effectiveness of the project-based learning approach in increasing students' entrepreneurial spirit. Methodology: The type of research used is quantitative research with an experimental design. The research sample was selected from two classes, each consisting of 30 students, so the total sample was 60 people. The data collection technique in this research will use a questionnaire. The data analysis technique in research uses comparative statistics in the form of the T-test. Main Findings: There is a difference in the entrepreneurial spirit of students who take part in learning with a project-based learning model and students who do not take part in learning with a project-based learning model with a Sig value. < 0.05, namely 0.041. Novelty/Originality of this study: The novelty of this research is a comprehensive evaluative approach to project-based learning in enhancing students' entrepreneurial spirit, which aims to provide a deeper understanding of its effectiveness.